Acute Oncology Service in Nepal: Current Status and Future Directions - Sah, Guru Sharan; Regmi, Yogesh; Sapkota, Simit; Tiwari, Sagar (Nepalese Journal of Cancer, 2025)
Cancer care in Nepal has witnessed a significant advancements, yet the management of oncological emergencies remains to have a critical gap. Acute Oncology Service (AOS) plays a pivotal role in ensuring timely interventions for patients facing cancer-related complications. This report highlights the current status of cancer care in Nepal, the urgent need for a structured AOS, and insights from the 4th BPKMCHCON conference, which focused on the establishment and expansion of AOS nationwide.The conference brought together national and international experts to discuss the integration of AOS, best practices, and sustainable strategies. The recommendations emphasize multidisciplinary collaboration, structured care pathways, and the necessity of nationwide implementation.